Fighting for farming justice : diversity, food access and the USDA - Jett, Terri (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book provides a detailed discussion of four class-action discrimination cases that have recently been settled within the United States Department of Agriculture (USDA) and have led to a change in the way in which the USDA supports farmers from diverse backgrounds. These settlements shed light on why access to successful farming has been so often limited to white men and/or families, and significantly this has led to a change for opportunities in the way the USDA supports famers from diverse backgrounds. With chapters focusing on each settlement Jett provides an overview of the USDA before diving into a closer discussion of the four key settlements, involving African American farmers (Pigford), Native Americans (Keepseagle), Woman famers (Love) and Latino(a) farmers (Garcia), and the similarities between each. This title places and emphasis on what is happening in farming culture today, drawing connections between these four settlements and the increasing attention on urban farming, community gardens, farmers markets, organic farming and the slow food movement, through to the larger issues of food justice and access to food. Fighting for Farming Justice will be of interest to scholars of food justice and the farming arena, as well as those in the fields of Agricultural Economics, Civil Rights Law and Ethic Studies"--
The politics of the U.S.D.A. and the Census of agriculture -- The challenges of the local structure of the U.S.D.A -- Pigford I and II : the case involving black farmers -- Situating the Keepseagle Settlement in tribal and food sovereignty -- The marriage of the Garcia and Love settlements -- Envisioning a more open USDA for the greater good.
OCLC-licensed vendor bibliographic record.
Keywords: United States. -- Department of Agriculture -- Management; Discrimination in agriculture -- United States; Minority farmers -- Civil rights -- United States; Class actions (Civil procedure) -- United States; Agricultural administration -- Social aspects -- United States; Agriculture and state -- United States; NATURE / Ecology; SOCIAL SCIENCE / Sociology / Rural